Power Saving in Open RAN by Using Advanced CPU Scheduling Algorithm - Urumkar, Saish; Sharma, Sachin (IEEE International Conference on Smart Computing (Online), 2025)
Open RAN is an emerging wireless technology that is gaining significant attention for its potential to enable flexible, cost-efficient, and interoperable networks. Reducing power utilization in Open RAN, particularly for 5G base stations (gNodeBs) deployed in remote areas, remains a critical challenge due to limited power availability. In our previous work, we developed a CPU scheduling algorithm that optimized core allocation based on load conditions, reducing power utilization for gNodeB in a virtualized Open RAN environment. Extending our previous work, this paper introduces an advanced CPU scheduling for Open RAN designed to reduce power utilization in real hardware Open RAN gNodeBs. The proposed algorithm for Open RAN is able to lower CPU power consumption by 10 to 11% maintaining bounded throughput, contributing to more energy-efficient Open RAN deployment.